Politeness Strategies in Georgian and English Languages: A Linguistic and Cultural Comparison (Based on Jane Austen’s Pride and Prejudice and its Georgian Translation) - Dzamiashvili, Elene; Nakhutsrishvili, Ekaterine ("Intercultural Dialogues" Transactions, 2025)
This paper examines how politeness strategies are expressed in English and Georgian, based on selected dialogues from Jane Austen’s Pride and Prejudice and its Georgian translation. Using a contrastive pragmatics approach, the study analyses how key speech acts – such as requests, refusals, apologies, compliments, and expressions of emotion – are realised in both versions. It focuses on how each language encodes politeness through social roles, communication norms, and interactional patterns. The findings reveal that while both English and Georgian cultures place value on interpersonal harmony, they achieve this goal through distinctly different means. English dialogue usually prefers to be indirect and careful in tone. Speakers often use soft or cautious language, avoid exaggeration, and keep a polite or emotionally distant style. This shows that English communication often values personal independence and respectful social behaviour. In contrast, Georgian favours expressiveness, directness within social boundaries, hierarchical sensitivity, and overt emotional engagement. These tendencies point to broader cultural scripts and contrasting views on how respect, solidarity, and authority are conveyed in interaction. This paper also shows how important the translator’s role is as a cultural bridge, especially in literature, where politeness is not only in the words but also in tone, style, and hidden meanings. Translating dialogue in fiction is particularly difficult because even small changes in politeness can affect how characters relate to each other. The study helps us better understand how different cultures communicate and shows why it is important to teach and learn how language works in real social situations – not just words, but meaning and context too.